2010
DOI: 10.2109/jcersj2.118.1195
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of hydroxyapatite nanoparticles with various counterions as templates

Abstract: Hydrothermal synthesis proves to be a feasible route to fabricate hydroxyapatite nanoparticles. The study reports the combinational effects of temperature and various counterions, such as SO 4 2¹, Cl ¹ , and K + , on the morphology of hydroxyapatite nanoparticles. The resultant nanoparticles are investigated using powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The results show that the effects of temperature and different counterions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…26 In that context, it was very important to establish a clear relationship between experimental conditions and particle morphology and crystallinity. The crystalline structures of the samples synthesized with different experimental conditions are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 In that context, it was very important to establish a clear relationship between experimental conditions and particle morphology and crystallinity. The crystalline structures of the samples synthesized with different experimental conditions are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that the HA nanoparticles with modified shape could be prepared by using the combined effects of temperature and counter ions, which are simple, inexpensive and eco-friendly. 23,26 Conclusions HA nanoparticles were successfully synthesized by hydrothermal method using friendly synthesis conditions. Due the conditions and experiments studied, homogeneous colloidal nanoparticles were obtained in their form and crystallinity, having a selective chemical composition, being this a reproducible and simpler method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium content in dBMS was measured using the ethylenediaminetetraacetic acid (EDTA) complexometric titration method 14 . For immunohistochemistry(IHC) of collagen type I (COLI), sections were performed with 0.1% trypsin without EDTA for 2 h at 37°C for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium content in dBMS was measured using the ethylenediaminetetraacetic acid (EDTA) complexometric titration method. 14 For immunohistochemistry(IHC) of collagen type I (COLI), sections were performed with 0.1% trypsin without EDTA for 2 h at 37 C for antigen retrieval. After blocking with 5% BSA for 1 h at room temperature, sections were incubated with primary rabbit anti-human COLI antibody (Servicebio, GB11022-1, 1:200, China) at 4 C overnight.…”
Section: Characteristics Of Dbmsmentioning
confidence: 99%